Efisiensi Pemasaran Lada Putih dan Lada Hitam di Desa Atolanu Kecamatan Lambandia Kabupaten Kolaka Timur - Syamsinar; Nurcayah; Basri Sufa (Agrisurya, 2024)
Pepper production in East Kolaka Regency has increased by 96 thousand tons in 2017 to 280 thousand tons in 2022. This condition illustrates that the potential for pepper farming is very promising, including in Lambandia District, Atolanu Village, East Kolaka Regency, which is the research location, contributing 15.86 tons. in 2022 from total pepper production. Even though pepper production tends to increase, people's interest in cultivating pepper agribusiness (black pepper and white pepper) is still relatively low compared to other commercial crops, this is due to a marketing system that sometimes takes a long time and creates risks and inefficient marketing costs. .The research aims to determine marketing channels and analyze the margins and efficiency of white pepper and black pepper from Atolanu Village, Lambandia District, Kolaka Regency. Sampling was carried out in groups (clusters) for white pepper and black pepper respondents, and by census for marketing actors. The data was analyzed using descriptive methods to determine the marketing channels for white pepper and black pepper and quantitatively to calculate the marketing margin M= He – Hp, and analyzing the level and efficiency or percentage of price received by farmers for both white and black pepper using the EP formula approach. =1 –( MP/( He) )X 100 %. The research results show that there are two marketing channels for white pepper and black pepper farming in Atolanu Village, Lambandia District, Kolaka Regency, marketing channel I starts from Farmers, PPD, PPK, Exporters with a margin of IDR 2,000/Kg, and marketing channel II starts from Farmers, PPD, and PPK with a margin of IDR 3,000/Kg. The level of efficiency of both marketing channels is efficient with an efficiency value of > 50% respectively, marketing channel I is 97.2% and marketing channel II is with an EP value of 95.5%.